Efficiency of the use of ryegrass by heifers in response to the receival of supplement - Laila Arruda Ribeiro; Marta Gomes da Rocha; Luciana Pötter; Maria José de Oliveira Sichonany; Mônique Foggiato da Silva; Anelise Pereira Hundertmarck (Acta Scientiarum. Animal Sciences, 2017)
The intensity and frequency of defoliation of ryegrass (Lolium multiflorum Lam.) by beef heifers exclusively grazing or receiving corn grain or extruded commercial product with fat as supplement were evaluated. The grazing method was put-and-take stocking. The experimental design was completely randomized following a repeated measure arrangement, three treatments and two area replications. The phyllochron of ryegrass was 140.1 and 303.4°GD the leaf lifespan. The intensity (67.0 %) and the frequency of defoliation (6.4 days) were similar, regardless of supply or no of energetic supplement for grazing heifers. The defoliation frequency indicates that the heifers can return about 3.3 times to the same tiller during the leaf lifespan. Considering the different categories of leaf blades, the supply of extruded fat causes the heifers to remove higher proportion (66.5 %) of expanding leaf blades. On ryegrass pasture, the efficiency of forage use is not modified when heifers receive energetic supplement.